2004
DOI: 10.1080/00016470410001259
|View full text |Cite
|
Sign up to set email alerts
|

Standing radiographs underestimate joint widthComparison before and after resection of the joint in 34 total knee arthroplasties

Abstract: BackgroundMeasurement or estimation of joint width is routinely used in the preoperative evaluation of gonarthrosis. To our knowledge, the validity and reproducibility of this procedure has not been adequately studied.Patients and methods We measured joint width in 34 knees (medial arthrosis: n = 22, lateral arthrosis: n = 12) on preoperative weight-bearing radiographs and on radiographs of the corresponding part of the joint after knee arthroplasty. The bone/cartilage pieces were placed in anatomical position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This result appears to be comparable to the results of some studies using the conventional technique ( Bathis et al 2004 , Perlick et al 2004 , Yau et al 2008 , Ng et al 2012 ), using CAS ( Kim et al 2007 , Yau et al 2008 ), and using PSPGs (only 1 study) ( Nam et al 2013 ). However, several studies using CAS ( Bathis et al 2004 , Perlick et al 2004 , Nam et al 2013 ) and PSPGs ( Ng et al 2012 , Daniilidis and Tibesku 2014 , Macdessi et al 2014 ) have reported fewer outliers. The preoperative MRI planning does not take into account soft tissue balancing, and some of the malalignments of the HKA angle might be explained by improper soft tissue balancing.…”
Section: Discussionsupporting
confidence: 86%
“…This result appears to be comparable to the results of some studies using the conventional technique ( Bathis et al 2004 , Perlick et al 2004 , Yau et al 2008 , Ng et al 2012 ), using CAS ( Kim et al 2007 , Yau et al 2008 ), and using PSPGs (only 1 study) ( Nam et al 2013 ). However, several studies using CAS ( Bathis et al 2004 , Perlick et al 2004 , Nam et al 2013 ) and PSPGs ( Ng et al 2012 , Daniilidis and Tibesku 2014 , Macdessi et al 2014 ) have reported fewer outliers. The preoperative MRI planning does not take into account soft tissue balancing, and some of the malalignments of the HKA angle might be explained by improper soft tissue balancing.…”
Section: Discussionsupporting
confidence: 86%
“…Perlick et al 20) inserted the femoral component in slight flexion of 2° to the anterior femoral cortex to avoid notching during navigated TKA. A preoperative radiological evaluation is essential.…”
Section: Discussionmentioning
confidence: 99%
“…The femoral cut should be modified during navigated TKA if remarkable anterior femoral bowing is detected. 20) …”
Section: Discussionmentioning
confidence: 99%
“…Buckland-Wright et al found in an arthrography-based study of knees with OA that JSW accurately estimated cartilage thickness in the medial but not in the lateral compartment [9]. In another study, knees obtained at joint replacement surgery for OA were compared with estimations of JSW by pre-surgical standing knee radiographs and significant differences between the radiologic measurement and surgical specimen measurement were observed in both medial and lateral arthrosis; however, lateral JSW measurements had a greater amount of variation of JSW by radiograph than did medial [10, 11]. There is also an acknowledged difference in the angle of the tibial plateau between medial and lateral compartments [12] which thus may make JSW estimates in the lateral compartment less accurate when read in radiographs optimized for assessment of the medial compartment.…”
Section: Introductionmentioning
confidence: 99%